Reinventing Chinese Tradition : The Cultural Politics of Late Socialism - Wu, Ka-ming (Book collections on Project MUSE., 2015)
"Yan-an, China was the main organizing site of Chinese communism from 1935 to 1949. As the final destination of the Long March and center of the 'red bases,' it acquired mythical status during the Maoist period as the symbol and epitome of the Communist Party's triumph. Yet in the post-Mao period, Yan-an's significance diminished, along with its role as an emblem of revolutionary heroism. In this study, Ka-ming Wu presents an ethnographic account of contemporary Yan-an. She looks at Yan-an today to see what happened to that society and culture in the post-socialism era. Wu examines new dynamics between state and society in light of how rural residents in northwest China make sense of rapid social changes. Under Mao, Yan'an's rural culture was stripped of its spiritual contents and reorganized around socialist, anti-imperial rhetoric to glorify communists' socioeconomic reforms. Since the 1980s, rural Ya'an has been reimagined as a hinterland of ancient cultural traditions. Wu documents how revivals of rural practices are reworked within the socialist legacy, including folk paper-cutting, a local form of musical storytelling, and spiritual cults of local deities. Even though Mao had repressed these practices, surprisingly their current revival has brought out the sacredness or urgency of the revolution's legacy. Instead of assuming that ascendent market forces have replaced state socialism, the dominant line about post-Mao China today, Wu probes the various cultural practices in contemporary Yan'an that evade total commercialization. She contends that this public realm contains powerful religious and ritual practices that produce new forms of meaning out of turbulent rural conditions and new dynamics of state-society relations in the post-socialist era"--